Antimicrobial susceptibility and molecular species identification of clinical carbapenem-resistant bacteria - MAULIN INGGRAINI; SITI NURFAJRIAH; JEPRI AGUNG PRIYANTO; Noor Andryan Ilsan (Society for Indonesian Biodiversity, 2021)
Abstract. Inggraini M, Nurfajriah S, Priyanto JA, Ilsan NA. 2021. Antimicrobial susceptibility and molecular species identification of clinical carbapenem-resistant bacteria. Biodiversitas 22: 555-562. Antibiotic is the first option treatment for infectious diseases both in human and animal. However, the excessive usage and misuse of antibiotics have driven antibacterial resistances worldwide and the increasing case of antibiotic resistance leads to limited options for treatment. This study aimed to observe antimicrobial susceptibility and molecular identification of carbapenem-resistant human clinical bacteria. A total of nine isolates in this study were collected in 2020 from a teaching hospital in Indonesia. All isolates were originated from various human clinical specimens, including urine, blood, pus, and sputum. Identification using 16s rRNA-based showed that these isolates were closely related to Klebsiella pneumoniae (1/9), A. baumannii (5/9), Escherichia coli (2/9), and Lysinibacillus fusiformis (1/9). According to minimum inhibitory concentration using Vitek Automated Machine, four isolates of multi-drug resistant (MDR) bacteria were found. In contrast, five of them were categorized as extensively-drug resistant (XDR). Interestingly, all of the XDR isolates belonged to A. baumannii. These isolates were resistant to at least seven different antimicrobial classes. A comparison of partial 16s rRNA showed two E. coli had similar variance. While in A. baumannii isolates, we found one of five isolates had a different variance sequence, which suggests different clonality among this species. This study gives an insight into the prevalence of carbapenem-resistant bacteria with XDR criteria in Indonesia.